PEREMPUAN DAN PERKOSAAN MEI 1998 DALAM DUA CERPEN KARYA SENO GUMIRA AJIDARMA: KRITIK SASTRA FEMINIS - Maretta Dwi Anjani; Y. Yulianeta; H. Halimah (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
The May 1998 rape is one of the historic events that has yet to be resolved. This event is portrayed in literary works as a sociocultural document. Seno Gumira Ajidarma as the author and journalist describes the incident through his short stories, namely